Template‐Assisted meta‐C−H Alkylation and Alkenylation of Arenes. (16th February 2017) - Bag, Sukdev; Jayarajan, Ramasamy; Mondal, Rahul; Maiti, Debabrata
Abstract: To expand the scope of meta ‐functionalization, a pyrimidine‐based template effective for the formation of β‐aryl aldehydes and ketones, using allyl alcohols, by meta ‐C−H activation of benzylsulfonyl esters is described. In addition, α, β‐unsaturated aldehydes were generated by in situ olefination and deprotection of allyl benzyl ethers. These new functionalizations at the meta ‐position of an arene have also been successfully implemented in benzylphosphonate, phenethyl carbonyl, and phenethylsulfonyl ester scaffolds. Key to these successful new functionalizations is the creation of an electropositive palladium center by accepting the electron cloud from the metal to the energetically low‐lying π‐orbitals of pyrimidine ring, and it favors coordination of allyl alcohol to the metal center.